The Role of Communication and Empathy in Building Emergency Patient Loyalty: A Mediation Study of Doctor-Patient Relationships - Harianto, Muhammad Imam Fitrah; Wahyudi, Bayu; Rubini, Rizki Adriansyah (Almana : Jurnal Manajemen dan Bisnis, 2025)
The Emergency Department (ER) plays a central role as the first point of contact for critically ill patients, shaping their initial perceptions of hospital service quality. This study investigated the impact of communication and empathy demonstrated by ER doctors at Cideres Regional Hospital, Majalengka, on patient loyalty, with the doctor-patient relationship as a mediating variable. Using an exploratory quantitative approach, this study aimed to identify the relationship between variables. The number of samples obtained in this study meets the minimum required number of samples, and the validity test of the instrument data uses the Pearson correlation method and the reliability test uses the Cronbach's Alpha test. The Sobel test was used in the mediation approach and the t-test for the influence approach. The results showed that all data instruments passed the validity and reliability tests, and all research hypotheses were accepted. It was found that doctor communication and empathy, both directly and mediated by the doctor-patient relationship, positively and significantly increased ER patient loyalty. Empathy was identified as the dominant variable. Increased positive patient perceptions of empathetic behavior of health workers or doctors significantly correlated with increased ER patient loyalty at Cideres Regional Hospital. These findings underscore the importance of healthcare workers, particularly doctors, demonstrating a high level of empathy and effective communication when providing services in the ER.